Integrated Management of Persistent Atrial Fibrillation - Xindi Yue; Ling Zhou; Chunxia Zhao (Biomedicines)
The global incidence of atrial fibrillation is on the rise. Atrial fibrillation, a complex disease, heightens the likelihood of heart failure, stroke, and mortality, necessitating careful attention. Controlling heart rate and rhythm, addressing risk factors, and preventing strokes are fundamental in treating atrial fibrillation. Catheter ablation stands out as the primary approach for atrial fibrillation rhythm control. Nevertheless, the limited success rates pose a significant challenge to catheter ablation, particularly for persistent atrial fibrillation. Various adjunctive ablation techniques are currently under investigation to enhance the effectiveness of catheter ablation. This review provides an overview of the current state of the art and the latest optimized treatments for persistent atrial fibrillation in the areas of rhythm control, heart rate control, and risk factor management.